Implementation of Fuzzy Logic in Detecting Air Temperature Based on Microcontroller - Harahap, Siti Sarah; Simamora, Windi Saputri; Hadistio, Ryan Rinaldi (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The environment, technology, and many facets of daily living are all significantly impacted by temperature conditions. Knowing environmental health, agriculture, industry, electrical technology, weather and natural disasters, transportation, and even scientific research are just a few of the many reasons why temperature conditions are crucial. Fuzzy algorithms are used to more flexibly process temperature data while creating a temperature detector employing fuzzy logic. We can base our conclusions on a wider range of criteria than merely right or wrong thanks to fuzzy logic. A temperature sensor, microprocessor, and display (such an LCD or LED screen) are some basic electronic components that can be used to create a temperature detector.